Spatial diversification of the regional expenses on culture in Poland 2003-2012 - Adam Mateusz Suchecki (Comparative Economic Research. Central and Eastern Europe, 2014)
Following the completion of the process of decentralization of the public administration in Poland in 2003, a number of tasks implemented so far by the state authorities were transferred to the local level. One of the most significant changes in the methods of financing and management of the local authorities was the transfer of culture and national heritage-related tasks to a group of the own tasks implemented by local governments. As a result of the decentralization process, the local government units in Poland were given a significant autonomy in determining the purposes of their budgetary expenditure on culture. At the same time they were obliged to cover these expenses from their own revenue. This paper focuses on the analysis of expenditure on culture covered by the provincial budgets, taking into consideration the structure of cultural institutions by their types in the years 2003, 2006, 2010 and 2012. To illustrate the diversity of the expenditure on culture by the type of the institutions in particular provinces, one applied the location quotient (LQ), which reflects a spatial distribution of expenditure on culture in relation to reference expenses incurred by the cultural institutions in Poland.
Keywords: 330; expenditure on culture; the provincial budgets; local finances; cultural institutions; location quotient (LQ)